International Plant Proteomics Organization (INPPO) World Congress 2014 - Joshua L. Heazlewood (Frontiers Research Topics, 2017)
The field of proteomics has advanced considerably over the past two decades. The ability to delve deeper into an organism's proteome, identify an array of post-translational modifications and profile differentially abundant proteins has greatly expanded the utilization of proteomics. Improvements to instrumentation in conjunction with the development of these reproducible workflows have driven the adoption and application of this technology by a wider research community. However, the full potential of proteomics is far from being fully exploited in plant biology and its translational application needs to be further developed. In 2011, a group of plant proteomic researchers established the International Plant Proteomics Organization (INPPO) to advance the utilization of this technology in plants as well as to create a way for plant proteomics researchers to interact, collaborate and exchange ideas. The INPPO conducted its inaugural world congress in mid 2014 at the University of Hamburg (Germany). Plant proteomic researchers from around the world were in attendance and the event marked the maturation of this research community. The Research Topic captures the opinions, ideas and research discussed at the congress and encapsulates the approaches that were being applied in plant proteomics.The field of proteomics has advanced considerably over the past two decades. The ability to delve deeper into an organism's proteome, identify an array of post-translational modifications and profile differentially abundant proteins has greatly expanded the utilization of proteomics. Improvements to instrumentation in conjunction with the development of these reproducible workflows have driven the adoption and application of this technology by a wider research community. However, the full potential of proteomics is far from being fully exploited in plant biology and its translational application needs to be further developed. In 2011, a group of plant proteomic researchers established the International Plant Proteomics Organization (INPPO) to advance the utilization of this technology in plants as well as to create a way for plant proteomics researchers to interact, collaborate and exchange ideas. The INPPO conducted its inaugural world congress in mid 2014 at the University of Hamburg (Germany). Plant proteomic researchers from around the world were in attendance and the event marked the maturation of this research community. The Research Topic captures the opinions, ideas and research discussed at the congress and encapsulates the approaches that were being applied in plant proteomics.